If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + -1(1 + -0.04) * 10 = x Combine like terms: 1 + -0.04 = 0.96 1 + -1(0.96) * 10 = x Multiply -1 * 0.96 1 + -0.96 * 10 = x Multiply -0.96 * 10 1 + -9.6 = x Combine like terms: 1 + -9.6 = -8.6 -8.6 = x Solving -8.6 = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -8.6 + -1x = x + -1x Combine like terms: x + -1x = 0 -8.6 + -1x = 0 Add '8.6' to each side of the equation. -8.6 + 8.6 + -1x = 0 + 8.6 Combine like terms: -8.6 + 8.6 = 0.0 0.0 + -1x = 0 + 8.6 -1x = 0 + 8.6 Combine like terms: 0 + 8.6 = 8.6 -1x = 8.6 Divide each side by '-1'. x = -8.6 Simplifying x = -8.6
| 5u^2+9u=-4 | | x+12=18-2x | | 3x-8=21 | | w^2-11wg+28g^2= | | x+2=98 | | 202-6x=39x+17 | | 2t^2+1t+1=0 | | 2x^2-20x+50=0 | | 54-19=5(x-5) | | 16x=4(3x+60) | | 3= | | c^2d+4cd^2=0 | | u^2+11u+28= | | 3x-1-5x+4= | | 4n+10= | | 23+9y=50 | | X+6y=5v | | 5x+3y+4=0 | | 7(6b-1)=-133 | | 6x+13=-17-9x | | 6n+5=29 | | (n-4)*8=16 | | 6(2-7x)=96 | | (n-6)*3=15 | | 60-(6x+4)=6(x+5)+x | | 3y-3+y+41=7y+40-5y | | 4(x-7)-2x-3(4x-2)-8=4-6(x-5)-36 | | 82=7+5(8-x) | | 9w^3-18w^2-315=0 | | 7y-10=6y-5 | | 8-(2x-3)=3(2-3x)-9 | | 8y-15=7y-14 |